The Effect of Population, GDP, Non-Renewable Energy Consumption and Renewable Energy Consumption on Carbon Dioxide Emissions in G-20 Member Countries - Islami, Fitrah Sari; Prasetyanto, Panji Kusuma; Kurniasari, Fitri (International Journal of Energy Economics and Policy, 2022)
The purpose of this study is to analyze the effect of population, Gross Domestic Product (GDP), consumption of non-renewable energy, and renewable energy on carbon dioxide (CO2) emissions in The G-20 Member Countries 2010-2019. The data used in this study is panel data. The data used in this study is secondary data obtained from the World Bank and BP Statistical Review of World Energy. This study uses panel data regression analysis through the E-views 11 program. The results of the analysis in this study show that (1) the population has a positive and significant effect on carbon dioxide (CO2) emissions in Thhe G-20 Member Countries, (2) Gross Domestic Product ( GDP) has a positive and insignificant effect on carbon dioxide (CO2) emissions in The G-20 Member States, (3) consumption of non-renewable energy has a positive and significant effect on carbon dioxide (CO2) emissions in The G-20 Member States, (4) consumption renewable energy has a negative and significant effect on carbon dioxide (CO2) emissions in The G-20 Member States, (5) Population variables, Gross Domestic Product (GDP), non-renewable energy consumption, and renewable energy consumption together have a significant effect on carbon dioxide (CO2) emissions in The G-20 Member Countries 2010-2019.